Group Counseling, Students’ Confidence, and Motivation in Arabic Language Learning at Islamic Higher Education Institution - Muslim; Pangidoan (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study aims to examine students’ perceived experiences of group counseling in relation to their confidence and motivation in Arabic language learning at STAI As-Sunnah Tanjung Morawa, an Islamic higher education institution in North Sumatra, Indonesia. This quantitative study involved 15 students who participated in group counseling. Data were collected through structured questionnaires, pre-test and post-test measurements, and post-intervention evaluations. Questionnaire data were analyzed using frequency and percentage distributions, while pre-test and post-test scores were analyzed using the Wilcoxon Signed-Ranks Test. The findings showed that 100% of students reported increased confidence, with 93.33% reporting very high confidence, and 100% reported that group counseling greatly increased their motivation to learn Arabic. Furthermore, 93.33% identified interactive discussion as the most helpful technique, 100% reported positive cooperation with group members, and 100% reported applying the learning techniques introduced during counseling. The broader pre-test and post-test analysis showed a statistically significant difference (Z = −3.304, p = .001). Overall, group counseling demonstrates potential as a complementary approach to Arabic language learning by supporting students’ confidence, motivation, interaction, collaboration, and learning strategies.